2021
DOI: 10.30588/jmp.v11i1.810
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Earning Per Share, Price to Book Value, Dividend Payout Ratio, and Net Profit Margin on the Stock Price in Indonesia Stock Exchange

Abstract: Fundamental analysis of companies with financial ratios is essential in making investment decisions for any company. Therefore, to obtain maximum profit, investors need to perform a study before making investment decisions. This research aims to examine the effect of Earning Per Share (EPS), Price to Book Value (PBV), Dividend Payout Ratio (DPR), and Net Profit Margin (NPM) on the stock price. The research at the Indonesia Stock Exchange, a sub-sector of food and beverage companies, period five years (2014-201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
18

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 32 publications
2
33
0
18
Order By: Relevance
“…Based on the results of the study, there is no significant effect of EPS, Current ratio, Debit to Equity, Cash flow Ratio on the stock prices of manufacturing companies listed in the Palestine Exchange in 2015-2020. It is worth to mention that many research studies in this area have revealed similar results (Asmirantho & Somantri, 2017;Bustani et al, 2021;Kamar, 2017;Musallam, 2018;Siregar & Doriawaty, 2021). Consequently, the researcher believes that there is a need to conduct more investigation to reveal the investor's behavior.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Based on the results of the study, there is no significant effect of EPS, Current ratio, Debit to Equity, Cash flow Ratio on the stock prices of manufacturing companies listed in the Palestine Exchange in 2015-2020. It is worth to mention that many research studies in this area have revealed similar results (Asmirantho & Somantri, 2017;Bustani et al, 2021;Kamar, 2017;Musallam, 2018;Siregar & Doriawaty, 2021). Consequently, the researcher believes that there is a need to conduct more investigation to reveal the investor's behavior.…”
Section: Discussionsupporting
confidence: 58%
“…Similarly, Asmirantho & Somantri (2017) discover that the ROE has no effect but positive on the stock price. In addition, Bustani et al (2021) point out that the Net Profit Margin does not significantly affect stock prices. Moreover, Utami & Darmawan (2019) conclude that debt to equity ratio, return on assets and return on equity partially have no effect on stock prices.…”
Section: Literature Reviewmentioning
confidence: 96%
See 3 more Smart Citations